Civilians and Military Supply in Early Modern Finland - Talvitie, Petri; Granqvist, Juha-Matti (Helsinki University Press, 2021)
During the early modern centuries, gunpowder and artillery revolutionized warfare, and armies grew rapidly. To sustain their new military machines, the European rulers turned increasingly to their civilian subjects, making all levels of civil society serve the needs of the military. This volume examines civil-military interaction in the multinational Swedish Realm in 1550-1800, with a focus on its eastern part, present-day Finland, which was an important supply region and battlefield bordered by Russia. Sweden was one of the frontrunners of the Military Revolution in the 16th and 17th centuries. The crown was eager to adapt European models, but its attempts to outsource military supply to civilians in a realm lacking people, capital, and resources were not always successful. This book aims at explaining how the army utilized civilians - burghers, peasants, entrepreneurs - to provision itself, and how the civil population managed to benefit from the cooperation. The chapters of the book illustrate the different ways in which Finnish civilians took part in supplying war efforts, e.g. how the army made deals with businessmen to finance its military campaigns and how town and country people were obliged to lodge and feed soldiers.